The dichotomy of electoral choice in fragmented societies: Prospects of 2023 Nigerian general elections - Adeyinka Patrick Adewumi (Masyarakat, Kebudayaan dan Politik, 2023)
Elections in fragmented states are usually contested along the divisive lines present within the geo polity, and this plays an important role in the emergence of political leaders. Nigeria, one of the most heterogeneous countries in the world, has exhibited predominantly ethnic voting since the consolidation of its fourth republic, and this has contributed to mixed socioeconomic and political fortunes. Using a qualitative approach based on secondary sources such as, books, journals, articles, this study highlights that mature democracies exhibit retrospective voting, through which objective scrutiny of government performance in the economy and other aspects of the state is done to determine whether to reward or punish political leaders at the polls. The limitations of primal and ethnic voting considerations in Nigeria, visible in development outcomes, call for a new guardrail to electoral choice. This paper argues the need for economic voting to predominate the ethnic considerations that determine electoral choice, as this can guarantee developmental outputs, and ensure political accountability that benefit the state. This study concludes that, if Nigeria is to experience significant changes in its fortunes going forward, the 2023 elections must change the narrative from non-evaluative considerations to evaluative voting considerations, for positive socioeconomic dividends.